PERAN USAHA KESEHATAN SEKOLAH DALAM PROMOSI KESEHATAN - Ari Rahmat Elsad; Gunawan Widjaja (Lembaga Penelitian Dan Pengabdian Masyarakat Institut Agama Islam Sultan Muhammad Syafiuddin Sambas Kalimantan Barat, 2022)
Health is the most important thing in life. Without health, living things cannot do much in doing something. Both physical and mental health really need to be maintained in carrying out a task in life. This study describes how health efforts in schools as a good program are used to promote school-based mental health during a pandemic. Search sources in journaling using Google Schoolar. The results of the study indicate that a planned, responsible and orderly health program can be a reference for promoting school-based mental health in the fight against COVID-19. This school health promotion program includes health education, health services, and fostering a healthy school environment. Effective and efficient school health promotion programs are supported by strong leadership and cross-sectoral collaboration. This is supported by three strengths, namely, institutions, cognitive frameworks, and social networks.